Filosofi Arca di Pura Sarin Bwana dalam Film Eksperimental: Kisah Perjalanan Sri Dalem Batu Putih dan Sri Dalem Batu Ireng di Desa Jimbaran - I Wayan Agus Mahardika (Samsara Institute Publisher, 2025)
In this research, we studied the statues at the Sarin Bwana Temple, Jimbaran Traditional Village. This statue has a strong appeal in terms of aesthetics and magical/religious cultural value orientation. The main problem is that the shape of the remaining statue is unclear and requires more detailed analysis. The aim of this research is to (1) analyze the aesthetic aspects of the Sarin Bwana Temple statue and (2) identify the harmony of magical and religious cultural values ​​in the statue. The method used in this research is a qualitative descriptive method based on djelantik aesthetic theory and functionalist theory. The research results show that the statues at Sarin Bwana Temple are rich in aesthetic symbolism and have shapes that reflect deep religious and magical values. The presence of the statue is not just a work of art, but also a means of preserving and realizing the cultural beliefs of the local community. This study provides a deeper understanding of the relationship between aesthetics, religious function, and cultural values ​​contained in these statues.